The impact of citizen participation and organizational commitment of faculty members at an Art University - Espinoza López , Luis Alberto (2025)
This research presents the results that we have extracted from the impact of citizen participation and the organizational commitment of teachers at an art university. Our objective is to determine the relationship that exists between citizen participation and the organizational commitment of ENSABAP teachers. Four specific objectives were established to analyze the relationship with institutional decision-making. Methodology: Our work methodology starts from a theoretical approach in which it is characterized by being descriptive, correlational, basic, non-experimental, with a quantitative and cross-sectional methodological approach. The Participation Behavior Questionnaire by Vergara and Hevia (2012) and the Organizational Commitment Questionnaire by Meyer et al. (1993) were used. These questionnaires were answered by 62% of the teachers who made up a non-probabilistic sample. Results: After analyzing the tests and processing the statistical data, the analysis did not identify a significant relationship between the variables. Discussion and Conclusions: The research allows us to affirm that citizen participation and the organizational commitment of the ENSABAP teachers do not have a significant relationship; therefore, there would be other factors for the teacher to be committed to the institution. Finally, this research contributes to showing the low levels of citizen participation and organizational commitment of the teachers of an art university. For all these reasons, it is necessary to strengthen citizen participation and organizational commitment in ENSABAP, so its importance is to provide the tools of democratic participation for the empowerment of teachers in decision making.